EVALUASI PELAKSANAAN SATU TAHUN JAMPERSAL DI KOTA TERNATE MALUKU UTARA TAHUN 2011: DESKRIPSI CAKUPAN JAMPERSAL - , INDRA SETYAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Comparison of Maternal Mortality Ratio (MMR) in developing countries compared with developed countries is 290 compared to 14 deaths per 100,000 live births. In Indonesia, Maternal Mortality Ratio (MMR) amounted to 228 per 100,000 live births, Infant Mortality Ratio(IMR) is 34 per 1,000 live births, and Neonatal Mortality Ratio(NMR) stands at 19 per 1,000 live births. Jaminan Persalinan as a new breakthrough in the achievement of the Millennium Development Goals of efforts implemented in Indonesia since 2011 to involve primary health centers as service center in Kota Ternate needs to be evaluated. Objective: This study aims to provide a one-year evaluation of the implementation of Jampersal in Ternate, North Maluku. Method: This research is quantitative descriptive study that collects secondary data from puskesmas profile from 2009 to 2011 and analyzed using univariate and bivariate analyzes to Jampersal scope and influence in reducing MMR and IMR. Result: Jampersalâs coverage evaluation that includes antenatal care